2013
DOI: 10.3892/ol.2013.1573
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and loss of heterozygosity detected in middle-aged patients with sporadic colon cancer: A retrospective study

Abstract: Microsatellite instability (MSI) is a mutator phenotype that results from a defective mismatch repair (MMR) pathway. The present study examined the incidence of MSI and loss of heterozygosity (LOH) according to five markers from the panel of the National Cancer Institute (NCI) in 38 colorectal cancer (CRC) patients from the United Arab Emirates (UAE). MSI and LOH were analyzed using fragment analyses in a multiplex PCR setting on a capillary array electrophoresis platform. The expression of the MMR proteins, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…3). This rate turned out to be lower as compared with frequency of MSI, which was determined by other researchers that probably is associated with different prevalence of MSI in different ethnic groups [28]. For instance, according to the literature, MSI is detected in 25-30% of all endometrial carcinomas [25].…”
Section: Resultsmentioning
confidence: 78%
“…3). This rate turned out to be lower as compared with frequency of MSI, which was determined by other researchers that probably is associated with different prevalence of MSI in different ethnic groups [28]. For instance, according to the literature, MSI is detected in 25-30% of all endometrial carcinomas [25].…”
Section: Resultsmentioning
confidence: 78%
“…Meanwhile, the presence of LOH in the primary tumour may also be predictive of lymph node metastasis [31] and poor prognosis [32] . Previous studies have revealed a significant association between LOH and cancer stage [33] ; however, the study by Szukala et al did not reveal the predictive value of LOH with respect to local relapse in patients with laryngeal carcinoma [25] . We demonstrate herein that LOH in patients with laryngeal carcinoma is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies performed on LOH/MSI in head and neck cancers, colon cancer, ovarian cancer, and in cervical cancer in different populations with unknown HIV-1 status, reported frequent LOH/MSI in many chromosomes, with LOH/MSI frequencies that varied from 17 to 90% (9, 17, 18, 21, 30, 51). However, in this study, the LOH/MSI frequencies vary from 13 to 79% (Table 5).…”
Section: Discussionmentioning
confidence: 94%
“…MSI is a locus-specific change in the length of a short tandem repeat of nucleotide sequence in tumor genomic DNA when compared to the length in the normal genomic DNA (e.g., derived from white blood cells) from the same patient (18). MSI is caused by mutational inactivation of genes involved in DNA damage-repair (19).…”
Section: Introductionmentioning
confidence: 99%